2020
DOI: 10.1007/s40675-020-00176-w
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea and the Kidney

Abstract: Purpose of Review There are some uncertainties about the interactions between obstructive sleep apnea (OSA) and chronic kidney disease (CKD). We critically reviewed recent studies on this topic with a focus on experimental and clinical evidence of bidirectional influences between OSA and CKD, as well as the effects of treatment of either disease. Recent Findings Experimental intermittent hypoxia endangers the kidneys, possibly through activation of inflammatory pathways and increased blood pressure. In humans,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…End-stage renal failure affects 57% of patients with OSAS [ 80 , 81 ]. Hypoxia, fluid retention, and rennin-angiotensin system activation are the key elements of the interconnection between OSAS and kidney failure, aggravating both conditions [ 82 , 83 ]. Nevertheless, not only can OSAS lead to kidney failure installation, but there is an inverse variant of this relation [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…End-stage renal failure affects 57% of patients with OSAS [ 80 , 81 ]. Hypoxia, fluid retention, and rennin-angiotensin system activation are the key elements of the interconnection between OSAS and kidney failure, aggravating both conditions [ 82 , 83 ]. Nevertheless, not only can OSAS lead to kidney failure installation, but there is an inverse variant of this relation [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…End-stage renal failure affects 57% of patients with OSAS [77,78]. Hypoxia, fluid retention, rennin-angiotensin system activation are the key elements of the OSAS and kidney failure interconnection, aggravating of both conditions [79,80]. Nevertheless, not only OSAS can lead to kidney failure installation -there is an inverse variant [81].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…The first reports dated back to 1985 when Millman et al found that patients with endstage renal disease (ESRD) showed a high risk for OSA [12]. Since then, a growing body of evidence has been gathered about the association between OSA and CKD from various epidemiological points of view (OSA in CKD, CKD in OSA, OSA in ESRD), and with different study designs (case series, cross-sectional, cohort studies and randomized controlled trials -RCTs), as well as studies on the effects of OSA on renal function in animal models [7,13,14]. Nevertheless, there is significant heterogeneity of the existing studies in terms of outcomes, which often leads to contradictory results.…”
Section: Coexistence Of Osa and Ckd: Different Sides Of The Same Coinmentioning
confidence: 99%